Search for Dark Matter Annihilation Signals in the H.E.S.S. Inner Galaxy Survey - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Armand, C.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; et al. (Physical Review Letters, 2022)
The central region of the Milky Way is one of the foremost locations to look for dark matter (DM) signatures. We report the first results on a search for DM particle annihilation signals using new observations from an unprecedented γ-ray survey of the Galactic Center (GC) region, i.e., the Inner Galaxy Survey, at very high energies (?100 GeV) performed with the H.E.S.S. array of five ground-based Cherenkov telescopes. No significant γ-ray excess is found in the search region of the 2014-2020 dataset and a profile likelihood ratio analysis is carried out to set exclusion limits on the annihilation cross section ?σv?
CRIS-Team Scopus Importer:2022-09-30